Implementation of Photonovel Media to Promote Student Literacy Science - Fatma Sukmawati (Jurnal Penelitian Pendidikan IPA, 2022)
Science and technology in the 21st century is developing very fast. This requires qualified, reliable, and globally competitive human resources. One of the skills needed in the 21st century is literacy science. This study aims to promote literacy science by using Photonovel as a medium. This type of research is an experiment with the One-Group Pretest-Posttest Design model. The research sample was 21 students of class VIII of SMP Kasatrian 1 Surakarta. Data collection methods used are tests, questionnaires, documentation, and observation. Data analysis was done descriptively and inferentially. The results showed an increase in students' scientific literacy skills in the high category, the average gain test included in the medium criteria, which was 0.8. Based on the explanation above, the use of the Photonovel media can improve students' Literacy science